2012
DOI: 10.1097/mpg.0b013e31825f4c3e
|View full text |Cite
|
Sign up to set email alerts
|

Serial Evaluation of Children With ALF With Advanced MRI, Serum Proinflammatory Cytokines, Thiamine, and Cognition Assessment

Abstract: Patients with ALF have CE contributed by raised brain glutamine and PCs. MBs are small because of thiamine deficiency and show recovery in follow-up. CE and brain glutamine recover earlier than normalization of NCT and liver functions. Persistence of raised cytokines up to 6 months after insult suggests possible contribution from liver regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 34 publications
(50 reference statements)
3
28
0
Order By: Relevance
“…In a previous study on experimental trauma/hemorrhagic shock in genetically identical mice, we observed a high degree of variability in the raw circulating mediator data, but could identify distinct principal inflammatory drivers in animals receiving hemorrhagic shock from those subjected to sham cannulation [11] . In the present study, we affirm that the inflammatory response of a diverse cohort of PALF participants is highly variable [20] [22] and that PCA could segregate inflammation patterns associated with different outcomes.…”
Section: Discussionsupporting
confidence: 78%
“…In a previous study on experimental trauma/hemorrhagic shock in genetically identical mice, we observed a high degree of variability in the raw circulating mediator data, but could identify distinct principal inflammatory drivers in animals receiving hemorrhagic shock from those subjected to sham cannulation [11] . In the present study, we affirm that the inflammatory response of a diverse cohort of PALF participants is highly variable [20] [22] and that PCA could segregate inflammation patterns associated with different outcomes.…”
Section: Discussionsupporting
confidence: 78%
“…The impact of inflammatory response, oxidative stress, and disturbances in neurotransmitter function and auto regulation of cerebral blood flow/metabolism during ALF is becoming increasingly clear 6 , 7 , 36 . A recent study in pediatric acute viral hepatitis patients, while very small, is consistent with adult literature in identifying cognitive deficits tied to indicators of cerebral edema, pro-inflammatory cytokines, and ammonia levels 8 . More detailed analysis of medical and demographic factors (such as SES)in a larger, longitudinally assessed cohort will be a priority to tease apart several potential contributors to cognitive outcomes in PALF.…”
Section: Discussionsupporting
confidence: 70%
“…Several small, single center studies in PALF survivors have examined cognitive function in specific disease groups including acute viral hepatitis (4), Wilson disease (27), and Reye syndrome (28), but these findings are difficult to generalize to the broader group of diagnoses that lead to PALF. Srivastava et al examined 6 children with HE and CE demonstrated on advanced MRI and correlated findings with serial neurocognitive testing after recovery.…”
Section: Discussionmentioning
confidence: 99%
“…(1) (2) (3) A small case series of children surviving PALF secondary to viral hepatitis demonstrated significant cognitive deficits that improved in parallel with indicators of CE and circulating pro-inflammatory cytokine levels. (4)…”
mentioning
confidence: 99%